2013
DOI: 10.2134/agronj2012.0223
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Irrigation Effects on Soil Aggregation and Carbon Pools in the Indian Sub‐Himalayas

Abstract: Carbon retention is a critical issue in arable farming of the Indian Himalayas. Th is study, conducted from 2001 through 2010 on a sandy clay loam soil, evaluated the eff ect of tillage alterations (conventional tillage [CT] and zero tillage [ZT]) and selected irrigation treatments (I1: pre-sowing, I2: pre-sowing + active tillering or crown root initiation, I3: pre-sowing + active tillering or crown root initiation + panicle initiation or fl owering, and I4: pre-sowing + active tillering or crown root initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…Bhattacharyya et al, 2013 found that small macro-aggregates accounted for >30% of the total aggregates (mean of both main plots) in the surface soil layer. Silt-plus clay-sized aggregates comprised the greatest proportion of the whole soil, followed by the small macro-aggregates.…”
Section: Carbon Content and Aggregate Stabilitymentioning
confidence: 90%
“…Bhattacharyya et al, 2013 found that small macro-aggregates accounted for >30% of the total aggregates (mean of both main plots) in the surface soil layer. Silt-plus clay-sized aggregates comprised the greatest proportion of the whole soil, followed by the small macro-aggregates.…”
Section: Carbon Content and Aggregate Stabilitymentioning
confidence: 90%
“…A higher Leaf Area Index (LAI) in the soil conservation practices than in the CT plots could be due to the compounded effects of many factors, such as an additional nutrient supply, decreased competition for resources due to a lower weed density, improved soil physical properties and water regimes, better radiation interception, water extraction, aeration and less evaporation in the soil conservation practices compared with the CT plots (Unger et al, 1998;Bhattacharya et al, 2012Bhattacharya et al, , 2013Das et al, 2014). Soil structure affects crop yield through a complex of root-based mechanisms, that in turn affect above-ground biomass (Passioura, 2002).…”
Section: à2mentioning
confidence: 99%
“…When the crop residues are retained on the soil surface, it initiates processes that lead to improved soil quality by protecting the soil from raindrops and limiting water evaporation. Therefore, CA may lead to sustainable improvements in the efficient use of water by increasing infiltration and soil water retention and reducing water losses due to evaporation, and by improving nutrient balances and their availability (Dahiya et al, 2007;Govaerts et al, 2007;Verhulst et al, 2010;Bhattacharya et al, 2013). CA also improves soil health (mainly by increasing SOM content).…”
Section: Introductionmentioning
confidence: 99%
“…Retention of green manures in rice helps to improve soil nutrient status and promotes soil microbial activity . These alternative practices are known to exert positive effects on chemical, physical and biological soil properties (Bhattacharyya et al, 2006(Bhattacharyya et al, , 2013a.…”
Section: Introductionmentioning
confidence: 99%